Effects of Financial Literacy and Digital Capital Access on MSMEs Financial Performance - Yatimin, Yatimin; Priharta, Andry; Musharianto, Adi; Budiasih, Yanti (Journal of Business Management and Economic Development, 2026)
This study aims to examine the effects of financial literacy and access to digital capital on the financial performance of micro, small, and medium enterprises (MSMEs) amid the increasing digitalization of financial services. Using a quantitative explanatory design, data were collected from MSME owners adopting digital financial services and analyzed using Structural Equation Modelling–Partial Least Squares (SEM-PLS). The results show that financial literacy has a positive and significant effect on MSME financial performance, indicating its important role in improving financial decision-making and business sustainability. Digital capital access also significantly enhances financial performance by improving liquidity and reducing financing constraints. Furthermore, the findings reveal that financial literacy and access to digital capital serve as complementary drivers of MSME performance. This study contributes to the literature by integrating financial literacy and digital capital access into a unified analytical framework in the digital finance context and provides practical implications for policymakers, financial institutions, and MSME actors to promote inclusive digital financial ecosystems and sustainable MSME growth.